COVID-19 Delta Variant Co-Infection Mimicking COVID-19 ARDS - James Crosby DO; Sarah Semon MD; Subramanya Shyam Ganti MD, MBBS; Enid Klauber-Choephel MD; James Abraham MD (SAGE Publishing, 2022)
The Delta variant of COVID-19 has been associated with severe disease causing a surge in the second half of 2021. Atypical pathogens can be present in those in particular with severe ARDS and can contribute to excess morbidity and mortality. We must maintain a high level of suspicion for these pathogens as this can present an opportunity to dramatically improve the prognosis of a patient with COVID-19 ARDS. However, lend caution to Mycoplasma IgM serology as this can be a false-positive. If suspicion remains high for Mycoplasma pneumoniae infection, sputum polymerase chain reaction (PCR) for M pneumoniae is the gold standard for diagnosis. We present the case of a 42-year-old female with COVID-19 Delta variant presumed ARDS who had co-infection with M pneumoniae confirmed by endotracheal sputum aspirate PCR with rapidly improving oxygenation and extubation within 4 days of effective antibiotic therapy.